1999
DOI: 10.1103/physrevc.59.1179
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation ofαparticles from the31Pnucleus

Abstract: The energy spectra of α-particles have been measured in coincidence with the evaporation residues for the decay of the compound nucleus 31 P, produced in the reaction 19 F (96 MeV) + 12 C. The data have been compared with the predictions of the statistical model code CASCADE. It has been observed that significant deformation effect in the compound nucleus need to be considered in order to explain the shape of the evaporated α-particle energy spectra.One of the main motivations of the low energy heavy ion react… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This is realized by varying only the radius parameter r • . The optimum value of r • is found to be ∼ 1.56 fm which is consistent with our earlier work [9]. The increased radius parameter lowers the emission barrier and hence enhances the low energy yield by increasing the transmission coefficients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is realized by varying only the radius parameter r • . The optimum value of r • is found to be ∼ 1.56 fm which is consistent with our earlier work [9]. The increased radius parameter lowers the emission barrier and hence enhances the low energy yield by increasing the transmission coefficients.…”
Section: Discussionsupporting
confidence: 90%
“…But our previous studies on the intermediate mass fragment emission did not reflect the existence of any such longlived dinuclear configuration [13,14] of the 31 P compound nucleus. Earlier, we have measured also α-particle spectra in coincidence with the evaporation residues in the 96 MeV 19 F on 12 C reaction [9] and have observed that the measured spectra deviate from the statistical model predictions both at low as well as at high energy sides. Assuming a deformed configuration of the compound nucleus, the full energy spectra could be explained satisfactorily.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…An orbiting dinuclear complex is assumed to be more deformed than a fully shape equilibrated CN; this motivated us to look for such enhanced deformation in a 16 O + 12 C dinuclear system at same excitation energies using the LCP spectroscopy technique. In this technique, LCPs, evaporated from the excited composites, are used to study the properties of hot rotating nuclear systems as a function of excitation energy, angular momentum, and deformation [11,[13][14][15][16][17][18][19][20][21][22][23][24][25] using statistical model codes, e.g., CASCADE [26], GANES [27], CACARIZO [28].…”
Section: Introductionmentioning
confidence: 99%